Can Well-sampled Phase Curves Be Used to Infer Asteroid Spectral Features? - Zachary Murray (The Planetary Science Journal)
The relationship of an asteroid's reduced magnitude to its phase has a long history of study. Included in this history have been efforts to study the correlation between these parameters and spectral type. However, these efforts often suffer from the inclusion of only a few asteroids, missing phase curve data, uncorrected rotational or apparitional aberrations, and other issues. In this paper, we build upon previous approaches and address these issues. Broadly, this paper is split into two parts. The first is primarily concerned with carefully deriving phase curve parameters using a combined data set from several different sources, including observations from Gaia, the Transiting Exoplanet Survey Satellite, Palomar Transient Factory, Asteroid Terrestrial-impact Last Alert System, and Asteroid Lightcurve Data Exchange Format database using an ellipsoidal model that can correct for rotational and apparitional effects. The second concerns itself with making predictions on that data set and quantifying what can and cannot be inferred from phase parameters, both as a function of the phase curve parameterization chosen and as a function of the chosen model. We find that, while individual spectral classes remain hard to infer from the phase curves, broader statements on the presence of absorption features can dependably be made.